Arms and Armour in Byzantine Art : Studies in Military Iconography, 11th - 15th Centuries - Grotowski,Piotr Ł., (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
This volume examines the iconography of military equipment in the art of the Orthodox milieu in the Middle Ages. The authors address various problems, such as the veracity of representations of military equipment, the issue of presence of archaisms in the artwork, and the meaning and symbolism of armour in the Byzantine world. Taken together, these studies offer valuable insights for archaeologists and art historians concerned with the legacy of the medieval world, and for scholars interested in the history of military equipment. Contributors are Andrea Babuin, Timothy G. Dawson, Dejan Gjorgjievski, Piotr Ł. Grotowski, Marka Tomić, and Mamuka Tsurtsumia.